Beading of injured axons driven by tension- and adhesion-regulated membrane shape instability. Issue 168 (29th July 2020) - Shao, Xueying; Sørensen, Maja Højvang; Xia, Xingyu; Fang, Chao; Hui, Tsz Hin; Chang, Raymond Chuen Chung; Chu, Zhiqin; Lin, Yuan
Abstract : The formation of multiple beads along an injured axon will lead to blockage of axonal transport and eventually neuron death, and this has been widely recognized as a hallmark of nervous system degeneration. Nevertheless, the underlying mechanisms remain poorly understood. Here, we report a combined experimental and theoretical study to reveal key factors governing axon beading. Specifically, by transecting well-developed axons with a sharp atomic force microscope probe, significant beading of the axons was triggered. We showed that adhesion was not required for beading to occur, although when present strong axon–substrate attachments seemed to set the locations for bead formation. In addition, the beading wavelength, representing the average distance between beads, was found to correlate with the size and cytoskeleton integrity of axon, with a thinner axon or a disrupted actin cytoskeleton both leading to a shorter beading wavelength. A model was also developed to explain these observations which suggest that axon beading originates from the shape instability of the membrane and is driven by the release of work done by axonal tension as well as the reduction of membrane surface energy. The beading wavelength predicted from this theory was in good agreement with our experiments under various conditions. By elucidating the essential physics behind axon beading, the current study could enhance our understanding of how axonal injury and neurodegeneration progress as well as provide insights for the development of possible treatment strategies.